Impact of place attachment on risk perception: exploring the multidimensionality of risk and the scale of risk - Bernardo, Fátima (2014)
The literature is inconclusive regarding the relationship between place attachment and risk perception. Place attachment relates to reduced risk perception in some contexts and higher levels in others. Furthermore, longitudinal studies have shown that this relationship can change over time. In order to elucidate this relationship, we explored the multidimensionality of risk perception using the Slovic et al. paradigm with three types of risks: environmental, social and economic. A sample of 157 residents reported both place attachment and perceived risk. The results show that place attachment contributes to amplifying high probability risks and attenuates the perception of low probability ones. The results further show that place attachment is associated with the “control of risk” dimension including “voluntariness” and “controllability”.